An oxygen self-sufficient NIR-responsive nanosystem for enhanced PDT and chemotherapy against hypoxic tumors. Issue 22 (13th May 2019) - Yang, Guoliang; Tian, Jia; Chen, Chao; Jiang, Dawei; Xue, Yudong; Wang, Chaochao; Gao, Yun; Zhang, Weian
Abstract : An oxygen self-sufficient NIR-responsive nanoplatform enhances the efficiency of synergistic treatments between PDT and chemotherapy in hypoxic tumors. Abstract : The efficacy of photodynamic therapy and chemotherapy is largely limited by oxygen deficiency in the hypoxic tumor microenvironment. To solve these problems, we fabricated a novel NIR-responsive nanosystem which could co-deliver oxygen and anticancer drug DOX. An oxygen self-sufficient amphiphile (F-IR780-PEG) was first synthesized and subsequently utilized to load anticancer drug DOX to form nanoparticles (F/DOX nanoparticles). Due to the high oxygen capacity of such nanoparticles, the hypoxic tumor microenvironment was greatly modulated after these nanoparticles reached the tumor region, and the results revealed that hypoxia-inducible factor α (HIF-1α) was down-regulated and the expression of P-glycoprotein (P-gp) was then reduced, which were in favor of chemotherapy. Under light irradiation at 808 nm, IR780 could efficiently produce singlet oxygen to damage cancer cells by photodynamic therapy (PDT). Simultaneously, the IR780 linkage could be cleaved by singlet oxygen generated by itself and resulted in DOX release, which further caused cell damage by chemotherapy. With the combination of PDT and chemotherapy, F/DOX nanoparticles showed remarkable therapeutic efficacy under in vitro and in vivo conditions. Furthermore, the F/DOX nanoparticles are favorable for imaging-guided tumor therapy due to the inherent fluorescence properties of IR780. We thus believe that the synergistic treatment described here leads to an ideal therapeutic approach to hypoxic tumors.